2018
DOI: 10.4103/ijnm.ijnm_57_18
|View full text |Cite
|
Sign up to set email alerts
|

Upfront skeletal muscle metastases from non-small cell lung carcinoma: Report of an extremely rare occurrence detected by 18F-fluorodeoxyglucose positron emission computed tomography scan

Abstract: Adenocarcinoma lung with upfront metastases to skeletal muscle is rarely encountered in clinical practice since skeletal muscles are highly resistant to dissemination from solid organs. Moreover, these muscle metastatic lesions generally present with pain and palpable mass to get detected clinically. However, silent skeletal muscle metastases without any symptoms or signs getting detected by functional imaging with whole body 18F-fluorodeoxyglucose positron emission/computed tomography (18FDG-PET/CT) scan have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…Lesions have also been reported in the orbit and pectoral muscles [7][8][9][10]. Besides, some literature also reports the calf muscles being among the common spreading sites [11]. Diagnosing metastasis to the skeletal muscles can be confusing as the symptoms can be misunderstood as muscle strain or injury.…”
Section: Discussionmentioning
confidence: 99%
“…Lesions have also been reported in the orbit and pectoral muscles [7][8][9][10]. Besides, some literature also reports the calf muscles being among the common spreading sites [11]. Diagnosing metastasis to the skeletal muscles can be confusing as the symptoms can be misunderstood as muscle strain or injury.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al [ 32 ] proposed that surgical resection or external radiotherapy should be considered for isolated masses without other metastases to reduce pain and mass effect. However, Purkayastha et al [ 33 ] reported a case of lung adenocarcinoma with left gluteus muscle metastasis in which acute metastasis of the lower back, bilateral supraspinatus muscle, and psoas muscle occurred after three cycles of personal computer chemotherapy and subsequent low-dose external radiotherapy. These clinical cases suggest that more clinical practice studies are needed for the diagnosis and treatment of SMM.…”
Section: Discussionmentioning
confidence: 99%